Portretne fotografije Marjana Kukca - Eiselt, Irena (Narodna in univerzitetna knjižnica, 2011)
In 2009, the Map and Pictoral Collection at the National and University Library of Slovenia bought 288 portrait photos of the most important Slovenian poets of the 20th century photographed by Marjan Kukec. Photos were taken between 1974 and 1981, when the Slovenska matica published France Pibernik’s books Med tradicijo in modernizmom (Between Tradition and Modernism (1978), and Med modernizmom in avantgardo – pričevanja o sodobni poeziji (Between Modernism and Avantgarde - Testimonies on Contemporary Poetry (1981). Marjan Kukec (1933-2019) was a painter, graphic artist, art teacher, photographer. He was a student of Evgen Sajovic, Božidar Jakac, and Marij Pregelj. He mastered several art techniques. His works are distinguished by a clear concept and carefully planned interpretation.In 2008, the Photographic Association of Slovenia awarded Kukec with the Janez Puhar Prize for his life’s work. He is a master of portrait photography. His photos reveal his clear conceptual approach to photography, and the ability to observe in-depth a portrayed person.
In 2009, the Map and Pictoral Collection at the National and University Library of Slovenia bought 288 portrait photos of the most important Slovenian poets of the 20th century photographed by Marjan Kukec. Photos were taken between 1974 and 1981, when the Slovenska matica published France Pibernik’s books Med tradicijo in modernizmom (Between Tradition and Modernism (1978), and Med modernizmom in avantgardo – pričevanja o sodobni poeziji (Between Modernism and Avantgarde - Testimonies on Contemporary Poetry (1981). In 2008, the Photographic Association of Slovenia awarded Kukec with the Janez Puhar Prize for his life’s work. He is a master of portrait photography. His photos reveal his clear conceptual approach to photography, and the ability to observe in-depth a portrayed person.